THE VALUE OF INDEPENDENT WORK OF STUDENTS IN MODERN CONDITIONS - Nasreddinova, Farzona (Журнал иностранных языков и лингвистики, 2021)
The article considers the value of independent work of students in the educational process which can show, that self-education - education obtained independently, outside the walls of any educational institution, without the help of a teacher; informal individual form of educational activity.